TESTING OF WATER QUALITY AT LAKE ŠODERICA IN VARAŽDIN COUNTY - Anita Ptiček Siročić; Doroteja Košćak; Dragana Dogančić (Journal of Chemists, Technologists and Environmentalists)
The rapid growth of industrial, agricultural, and urban areas, along with rising living standards, invariably results in an increase in the amount of solid, liquid, and gaseous waste elements in water. Because of the variety of hazards that recreational waters pose to human health and well-being, a thorough evaluation of the sources and relative importance of the resulting health effects is necessary.  The testing of bathing water quality was conducted by determination of physical-chemical indicators at three locations in the lake Šoderica in Varaždin county. Lake Šoderica is an artificial lake formed by quarries and also used as a swimming area. The results demonstrated that the water was suitable for swimming and that all examined criteria agreed with the legislation. The results of the analyzed physical-chemical parameters show that the bathing water is satisfactory, but it is also necessary to determine the microbiological parameters.